The philosophy of rights - Raburski, Tomasz (Acta Universitatis Lodziensis. Folia Iuridica, 2017)
Rights are one of the fundamental concepts in philosophy of law, ethics, and political philosophy. However, in Polish language the general research on rights has been neglected. Most of the scholars are concerned with the specific kinds of rights (e.g. human rights, constitutional rights) and not rights as a basic philosophical concept. This article investigates the differences between Polish and English theoretical discourses on rights. It stresses the philosophical importance of this concepts and outlines the crucial issues that have to addressed.